Квакша дальневосточная — Hyla japonica (Gunt.) (Anura, Hylidae) на Сахалине - Басарукин, А.М.; Боркин, Л.Я. (Вестник зоологии, 1975)
Four tree-frogs Hyla japonica (Günther) were caught on the 27th of July, 1973. in Sakhalin (settlement Kostromskoye, Kholmsk region). A description of specimens and zoogeographical estimate of this finding are given. A map of the tree-frog findings in Sakhalin, Kunashir and Khpkkaido is suggested.